The Association Between Anemia Knowledge Among Pregnant Women and Adherence to Iron and Folic Acid Supplementation with the Risk of Delivering a Stunted Infant in the Catchment Area of the Langgudu Community Health Center - Indri Indri; Alkhair Alkhair; Dea Zara Avila; Muammar Iksan (MESINA (Medical Scientific Journal), 2026)
Stunting remains a chronic nutritional problem that requires serious attention, including in the working area of Langgudu Public Health Center. Maternal health conditions during pregnancy, particularly knowledge of anemia and adherence to consuming iron-folic acid supplementation or blood supplement tablets, are suspected to be associated with the risk of giving birth to a stunted child. This study aimed to analyze the relationship between pregnant women’s knowledge of anemia and their level of adherence to consuming blood supplement tablets with the risk of giving birth to a stunted child in the working area of Langgudu Public Health Center. This study used a quantitative analytical observational method with a case-control design. The sample consisted of 186 respondents, including 93 mothers with stunted children as the case group and 93 mothers with children with normal growth status as the control group. Primary data were collected using questionnaires and observation sheets, while secondary data were obtained from the public health center’s nutritional status monitoring reports. Data were analyzed using the Chi-Square test. The results showed that pregnant women’s knowledge of anemia was not significantly associated with stunting incidence (p = 0.281). In contrast, adherence to consuming blood supplement tablets showed a significant association with stunting incidence (p = 0.003; OR = 0.404). Therefore, pregnant women’s adherence to consuming blood supplement tablets is an important factor related to the risk of giving birth to a stunted child. Accordingly, strengthening education, monitoring blood supplement tablet consumption, and providing nutritional counseling during pregnancy need to be improved.